Experimental glioma with high bHLH expression harbor increased replicative stress and are sensitive toward ATR inhibition. Issue 1 (10th September 2020) - Koch, Marilin Sophia; Czemmel, Stefan; Lennartz, Felix; Beyeler, Sarah; Rajaraman, Srinath; Przystal, Justyna Magdalena; Govindarajan, Parameswari; Canjuga, Denis; Neumann, Manfred; Rizzu, Patrizia; Zwirner, Stefan; Hoetker, Michael Stefan; et al.
Abstract: Background: The overexpression of (basic)helix-loop-helix ((b)HLH) transcription factors (TFs) is frequent in malignant glioma. We investigated molecular effects upon disruption of the (b)HLH network by a dominant-negative variant of the E47 protein (dnE47). Our goal was to identify novel molecular subgroup-specific therapeutic strategies. Methods: Glioma cell lines LN229, LNZ308, and GS-2/GS-9 were lentivirally transduced. Functional characterization included immunocytochemistry, immunoblots, cytotoxic, and clonogenic survival assays in vitro, and latency until neurological symptoms in vivo. Results of cap analysis gene expression and RNA-sequencing were further validated by immunoblot, flow cytometry, and functional assays in vitro. Results: The induction of dnE47-RFP led to cytoplasmic sequestration of (b)HLH TFs and antiglioma activity in vitro and in vivo. Downstream molecular events, ie, alterations in transcription start site usage and in the transcriptome revealed enrichment of cancer-relevant pathways, particularly of the DNA damage response (DDR) pathway. Pharmacologic validation of this result using ataxia telangiectasia and Rad3 related (ATR) inhibition led to a significantly enhanced early and late apoptotic effect compared with temozolomide alone. Conclusions: Gliomas overexpressing (b)HLH TFs are sensitive toward inhibition of the ATR kinase. The combination of ATR inhibition plus temozolomide or radiation therapy in this molecular subgroup are warranted.